Investigating SARS-CoV-2 breakthrough infections per variant and vaccine type - Dingemans, Jozef; van der Veer, Brian M. J. W.; Gorgels, Koen M. F.; Hackert, Volker; den Heijer, Casper D. J.; Hoebe, Christian J. P. A; Savelkoul, Paul H. M.; van Alphen, Lieke B. (Frontiers in Microbiology, 2022)
Breakthrough SARS-CoV-2 infections have been reported in fully vaccinated individuals, in spite of the high efficacy of the currently available vaccines, proven in trials and real-world studies. Several variants of concern (VOC) have been proffered to be associated with breakthrough infections following immunization. In this study, we investigated 378 breakthrough infections recorded between January and July 2021 and compared the distribution of SARS-CoV-2 genotypes identified in 225 fully vaccinated individuals to the frequency of circulating community lineages in the region of South Limburg (The Netherlands) in a week-by-week comparison. Although the proportion of breakthrough infections was relatively low and stable when the Alpha variant was predominant, the rapid emergence of the Delta variant lead to a strong increase in breakthrough infections, with a higher relative proportion of individuals vaccinated with Vaxzevria or Jcovden being infected compared to those immunized with mRNA-based vaccines. A significant difference in median age was observed when comparing fully vaccinated individuals with severe symptoms (83 years) to asymptomatic cases (46.5 years) or individuals with mild-to-moderate symptoms (42 years). There was no association between SARS-CoV-2 genotype or vaccine type and disease symptoms. Furthermore, the majority of adaptive mutations were concentrated in the N-terminal domain of the Spike protein, highlighting its role in immune evasion. Interestingly, symptomatic individuals harbored significantly higher SARS-CoV-2 loads than asymptomatic vaccinated individuals and breakthrough infections caused by the Delta variant were associated with increased viral loads compared to those caused by the Alpha variant. In addition, we investigated the role of the Omicron variant in causing breakthrough infections by analyzing 135 samples that were randomly selected for genomic surveillance during the transition period from Delta to Omicron. We found that the proportion of Omicron vs. Delta infections was significantly higher in individuals who received a booster vaccine compared to both unvaccinated and fully vaccinated individuals. Altogether, these results indicate that the emergence of the Delta variant and in particular Omicron has lowered the efficiency of particular vaccine types to prevent SARS-CoV-2 infections and that, although rare, the elderly are particularly at risk of becoming severely infected as the consequence of a breakthrough infection.